Accomplishing Impact by Performing Our Theories: It Can Be Done, Though Not Easily. (March 2020) - Bartunek, Jean M.
The expectation that scholarly research should have some impact on practice is being increasingly embraced, though how much this should be and what form impact should take are not often considered as thoroughly as they might be. In this article, I expand understandings and appreciation of the potential in impact by exploring the performativity of social science theories. I present three cases of academics performing their own theories in practice settings and explore some of the components, outcomes, and complexities of these performances. The cases include Elizabeth Warren's creation of the Consumer Financial Protection Bureau, Michael Porter's Five Forces model, and David Cooperrider's Appreciative Inquiry. Based on the cases, I suggest the value of enhanced recognition of the possibilities of impact.